Assessment of Policy and Access to HIV Prevention, Care, and Treatment Services for Men Who Have Sex With Men and for Sex Workers in Burkina Faso and Togo. (1st March 2015) - Duvall, Sandra; Irani, Laili; Compaoré, Cyrille; Sanon, Patrice; Bassonon, Dieudonne; Anato, Simplice; Agounke, Jeannine; Hodo, Ama; Kugbe, Yves; Chaold, Gertrude; Nigobora, Berry; MacInnis, Ron
Abstract : Background: In Burkina Faso and Togo, key populations of men who have sex with men (MSM) and sex workers (SW) have a disproportionately higher HIV prevalence. This study analyzed the 2 countries' policies impacting MSM and SW; to what extent the policies and programs have been implemented; and the role of the enabling environment, country leadership, and donor support. Methods: The Health Policy Project's Policy Assessment and Advocacy Decision Model methodology was used to analyze policy and program documents related to key populations, conduct key informant interviews, and hold stakeholder meetings to validate the findings. Results: Several policy barriers restrict MSM/SW from accessing services. Laws criminalizing MSM/SW, particularly anti-solicitation laws, result in harassment and arrests of even nonsoliciting MSM/SW. Policy gaps exist, including few MSM/SW-supportive policies and HIV prevention measures, e.g., lubricant not included in the essential medicines list. The needs of key populations are generally not met due to policy gaps around MSM/SW participation in decision-making and funding allocation for MSM/SW-specific programming. Misaligned policies, eg, contradictory informed consent laws and protocols, and uneven policy implementation, such as stockouts of sexually transmitted infection kits, HIV testing materials, and antiretrovirals, undermine evidence-based policies. Even in the presence of a supportive donor and political community, public stigma and discrimination (S&D) create a hostile enabling environment. Conclusions: Policies are needed to address S&D, particularly health care provider and law enforcement training, and to authorize, fund, guide, and monitor services for key populations. MSM/SW participation and development of operational guidelines can improve policy implementation and service uptake.